Ambulance diversion and its use as an ED overcrowding mitigation strategy: Does it work? A scoping review - Jin Han Malcolm Ong; Bernard J. W. Lim; Muhammad Ariffin B. M. Zahrin; Isaac J. S. Yong; Luke L. L. Tan; Ren Hao Desmond Mao; Marcus E. H. Ong; Fahad Javaid Siddiqui (International Journal of Emergency Medicine)
Abstract Objective Emergency department (ED) overcrowding is a worldwide issue with significant negative consequences, including increased patient mortality. Ambulance diversion (AD) is sometimes used as an intervention to momentarily relieve overcrowded EDs, however, jury is still out about the negative consequences both for emergency medical services (EMS) who are required to divert to an alternative destination, and for patients whose care is delayed. Additionally, there is no operational guidance to best operationalize AD. The objective of this scoping review was to collate and organize the peer-reviewed published literature on the effects of both diversion and diversion aversion measures, on emergency medical services (EMS) and patient outcomes. Method A systematic, comprehensive search was conducted in various databases to identify relevant studies. Medline, Embase, CINAHL, Psychinfo, Cochrane and ClinicalTrials.gov databases were searched. Online ACEP and NAEMSP portals were also searched. Included studies discussed AD in the setting of ED overcrowding that reported either EMS or patient outcomes. The effects of interventions implemented to reduce AD were also reported. Two independent reviewers screened the articles and consensus was reached when disagreements arose. Results Out of 10,061 identified records, 95 papers meeting the inclusion criteria contributed to the results. 51 were observational, 16 simulation, 15 interventional, 10 descriptive, 2 systematic reviews and 1 mixed method. 12 articles reported negative EMS outcomes compared to only 2 neutral or positive EMS outcomes. 19 articles reported negative patient outcomes, whereas 9 reported neutral or positive outcomes. 34 articles reporting on intervention attempts to reduce diversion found overall positive results with diversion aversion. Only 7 articles studied the qualitative effects of diversion. Conclusion There is no conclusive evidence on the effects of AD on EMS and patient outcomes. 31 articles reported negative EMS or patient outcomes with 11 articles reporting neutral or positive outcomes. Measures to reduce or avoid diversion, however, showed overall positive trend in the results when diversion was averted. More research to ascertain accurate effects with standardised criteria for outcomes is required. Qualitative outcomes were also not well reported and further research should be conducted to determine the psychological impact on both staff and patients.